Biochemical and biophysical studies of the prokaryotic proton dependent oligopeptide transporters - Solcan, N (2013)
The proton dependent oligopeptide transporters (POT family) are members of the Major Facilitator Superfamily of secondary active transporter proteins. They use the transmembrane proton gradient to drive the uptake of di- and tripeptides into the cytoplasm. Members of the family are highly conserved in pro- and eukaryotic genomes, and in humans they are responsible for the oral absorption of many drug families, including β-lactam antibiotics. Recently, the crystal structures of PepTSo and PepTSt, two prokaryotic homologues of the human proteins PepT1 and PepT2, captured the proteins in two distinct conformations, providing insight into the structural aspects of the transport mechanism. A protocol was designed for functional liposome reconstitution of POT proteins, and transport assays were conducted to characterise their substrate specificity, pH dependence and kinetic properties. Using site-directed mutagenesis, we identified binding site residues involved in peptide recognition and proton translocation, and distinguished between the two roles by comparing protein activity in proton- and peptide-driven conditions. We also investigated the roles of key residues in the conformational transitions that accompany the transport cycle, using data from biochemical assays, molecular dynamics simulations and modeling, as well as electron paramagnetic resonance measurements. In addition, several bacterial POT members were screened for crystallisation, in order to assess their stability and crystal diffraction quality in different detergents. Further work was performed with bacterial POT homologues YdgR and GkPOT, including binding studies using NMR spectroscopy and assaying drug transport in vivo and in vitro. Together, the data establish bacterial POTs as model systems for studying the mammalian oligopeptide transporters, and a mechanistic model for peptide transport is proposed.